The Imitation Game and the Nature of Mixed Methods. (October 2017) - Collins, Harry; Evans, Robert; Weinel, Martin; Lyttleton-Smith, Jennifer; Bartlett, Andrew; Hall, Martin
We describe the Imitation Game, a new research method that collects both qualitative and quantitative data, and which can be used as a mixed methods procedure in many disciplines. Drawing on two projects, one investigating gender, the other sexuality, we show that the quantitative and qualitative aspects of the Game combine in four different ways, from more quantitative to more qualitative, involving increasing cultural understanding by the researchers. Crucially, deep cultural input is initially supplied by the players of the Game, who act as "proxy researchers, " enabling data to be gathered quickly and efficiently. The analysis has its roots in sociology of scientific knowledge and studies of expertise and experience, hence the emphasis on the cultural foundations of methods and the nature of expertise.